2016
DOI: 10.1177/0022034516647713
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Microglial P2Y12 Signaling in Tongue Cancer Pain

Abstract: To elucidate if microglial P2Y12 receptor (P2Y12R) mechanisms are involved in the trigeminal spinal subnucleus caudalis (Vc; also known as the medullary dorsal horn) in intraoral cancer pain, we developed a rat model of tongue cancer pain. Squamous cell carcinoma (SCC) cells were inoculated into the tongue of rats; sham control rats received the vehicle instead. Nociceptive behavior was measured as the head-withdrawal reflex threshold (HWRT) to mechanical or heat stimulation applied to the tongue under light a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Recent studies have demonstrated that neuronal hyperexcitability in the orofacial pain transmission pathway contributes to persistent orofacial pain mechanisms following orofacial pathogenesis [4][5][6]. This pathway extends from the orofacial region to the pain information-processing region in the cerebrum and is associated with the pathological plastic changes in satellite glial cells in the trigeminal ganglion (TG), secondary neurons, microglia, and astrocytes in the Vc and C1-C2.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that neuronal hyperexcitability in the orofacial pain transmission pathway contributes to persistent orofacial pain mechanisms following orofacial pathogenesis [4][5][6]. This pathway extends from the orofacial region to the pain information-processing region in the cerebrum and is associated with the pathological plastic changes in satellite glial cells in the trigeminal ganglion (TG), secondary neurons, microglia, and astrocytes in the Vc and C1-C2.…”
Section: Introductionmentioning
confidence: 99%
“…Microglial P2Y12 receptor is also reported to be involved in the central sensitization of orofacial pain [93]. In a tongue cancer, pain model produced by squamous cell carcinoma (SCC) cell inoculation, microglia were strongly activated in TSNC, and administration of MRS2395 or minocycline reversed the associated nociceptive behavior and microglial activation in SCC-inoculated rats.…”
Section: Purinergic Signaling In Trigeminal Subnucleus Caudalis (Tsnc)mentioning
confidence: 99%
“…This resulted to be associated with increased excitability of nociceptive neurons and consequent allodynia after mechanical stimulation. The administration of the P2Y 12 antagonist MRS2395 strongly reduced the “nocifensive” behavior and microglial activation in these animals ( Tamagawa et al, 2016 ).…”
Section: P2y 12 Receptor Expression and Function Imentioning
confidence: 99%